ASSOCIATION OF EARLY CHILDHOOD CARIES AND NUTRITIONAL STATUS AMONG 5-YEAR-OLD CHILDREN IN INDONESIA - Nuzulisa Zulkifli; Anton Rahardjo; Risqa Rina Darwita; Melissa Adiatman; Diah Ayu Maharani; Sri Susilawati (Fakultas Kedokteran Gigi Unjani, 2022)
ABSTRACT Oral health and nutrition problems in children cannot be separated. Both share the same risk factors. The high prevalence of malnutrition and Early childhood caries (ECC) in developing countries, especially in Indonesia, still needs attention. This study aims to analyze the relationship between ECC and the nutritional status of children aged five years in Indonesia based on the 2018 Riskesdas data. The study used a cross-sectional study using secondary data from Riskesdas 2018. A sample of 701 children aged five years was subjected to clinical examinations and questionnaires. ECC as the independent variable and other risk factors; self-reported oral health, gender, mother's education level, father's employment status, family economic status, children's dietary practices, and utilization of health facilities were analyzed against nutritional status based on weight/height categories converted by Z-score. Results showed that the chi-square test showed a significant correlation between ECC, maternal education level, family economic status and dietary practices at risk of children on nutritional status (p-value <0.05). Multinomial logistic regression test proved a significant correlation between ECC and wasting (OR = 1.352, 95% CI: 0.989 – 2.589). ECC is not correlated with obesity. The conclusion is ECC can cause wasting in children. Meanwhile, several risk factors for nutritional problems and dental caries were similar. DOI : 10.54052/jhds.v2n2.p235-256